Thermal neutron radiative capture on cadmium as a counting technique at the INES beam line at ISIS: A preliminary investigation of detector cross-talk. (December 2017) - Festa, G.; Grazzi, F.; Pietropaolo, A.; Scherillo, A.; Schooneveld, E.M.
Abstract: Experimental tests are presented that assess the cross-talk level among three scintillation detectors used as neutron counters exploiting the thermal neutron radiative capture on Cd. The measurements were done at the INES diffractometer operating at the ISIS spallation neutron source (Rutherford Appleton Laboratory, UK). These tests follow a preliminary set of measurements performed on the same instrument to study the effectiveness of this thermal neutron counting strategy in neutron diffraction measurements, typically performed on INES using squashed 3 He filled gas tubes. The experimental data were collected in two different geometrical configurations of the detectors and compared to results of Monte Carlo simulations, performed using the MCNP code. Highlights: Experimental work on 3 He replacement for thermal neutron scattering applications. Follow up of a first proof of concept on the proposed approach based on radiative neutron capture on 113 Cd. Investigation of the cross talk level among three close lying detectors. Assessment of the effectiveness of a detector geometrical configuration (developed by some of the present authors) in use for epithermal neutron spectroscopy at the ISIS spallation neutron source (VESUVIO spectrometer) also for neutron diffraction.